The 2009/10 drought in China: possible causes and impacts on vegetation - Barriopedro Cepero, David; Gouveia, Célia M.; Trigo, Ricardo M.; Lin, Wang (American Meteorological Society, 2012)
© 2012 American Meteorological Society. This study received support from the EU 7th Framework Program (FUME) Contract Number 243888 and from Portuguese Science Foundation (FCT) through the ENAC PTDC/AAC-CLI/103567/2008 project. LW is supported jointly by the Chinese Academy of Sciences (Grant KZCX2-EW-QN204) and the National Natural Science Foundation of China (Grant 41025017). We thank J. L. Chen for calculating the water vapor flux and J. Cao for helpful discussions. The NDVI dataset was kindly supplied by VITO database (http://free.vgt.vito.be), USDA/FAS/OGA and NASA Global Agriculture Monitoring (GLAM) Project. Precipitation data were provided by the GPCC (http://gpcc.dwd.de). The hydroelectrical power production data were provided by the China National Knowledge Infrastructure (CNKI; http://www.cnki.net). NCEP-NCAR reanalysis were supplied by the NOAA/OAR/ESRL PSD at http://www.esrl.noaa.gov/psd/. Two anonymous reviewers provided helpful comments that contributed to improve the manuscript. Several provinces of China experienced an intense drought episode during 2009 and 2010. The drought was particularly severe in southwestern and northern China, where the accumulated precipitation from May 2009 to April 2010 was about 25% less than normal. The decline of accumulated precipitation over northern China was mostly noticeable during the summer season of 2009 and it was comparable to recent dry episodes. The southwestern China drought resulted from a sequence of dry months from summer 2009 to winter 2010, corresponding to the driest event since at least 1951. The suppression of rainfall in summer over both regions was in agreement with a weakened broad-scale South Asian summer monsoon, possibly influenced by an El Nino developing phase, whereas the extremely negative phases of the Arctic Oscillation during the winter of 2010 may have contributed to the persistence of the drought in southwestern China. The assessment of the associated impacts indicates that water reservoirs were severely affected with a similar ...